Microcephalic osteodysplastic primordial dwarfism type II: a child with unusual symptoms and clinical course; a case report - Spranger, Stephanie; Tariverdian, Gholamali; Albert, Friedrich; Sontheimer, Dieter; Zöller, Joachim E.; Weber, M.; Tröger, Jochen (European journal of pediatrics, 1996)
We report on a 13-month old boy with microcephalic osteodysplastic primordial dwarfism (MOPD), whose radiographic signs correspond with type II of this entity. Some of his clinical signs, such as the anomalies of the external genitalia and the urinary tract, are common to this subgroup of MOPD, but he also shows unusual clinical signs including bilateral knee dislocation and hypoplasia of the anterior corpus callosum. His clinical course was unusual with several episodes of breathing difficulties and increased intracranial pressure secondary to craniosynostosis at the age of 16 months. After fronto-orbital advancement for the treatment of brachycephaly, his psychomotor development improved remarkably.